2003
DOI: 10.1093/aje/kwg051
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Lower Urinary Tract Symptoms in a Population-based Sample of African-American Men

Abstract: Previous epidemiologic studies evaluating risk factors for lower urinary tract symptoms (LUTS) have focused on White populations. Between September 1996 and January 1998, in a population-based sample of African-American men aged 40-79 years in Flint, Michigan, the authors assessed the role of putative sociodemographic, lifestyle, and medical history risk factors in moderate to severe LUTS, including the subcategories of obstructive and irritative symptoms. After the exclusion of men with prostate cancer or pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
180
5
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(203 citation statements)
references
References 52 publications
13
180
5
5
Order By: Relevance
“…Significant relation between BMI (overweight men) and male LUTS was reported in some studies 17,18 , but not in other studies [19][20][21] . The study design and the study population differed among these reports.…”
Section: Discussionmentioning
confidence: 81%
“…Significant relation between BMI (overweight men) and male LUTS was reported in some studies 17,18 , but not in other studies [19][20][21] . The study design and the study population differed among these reports.…”
Section: Discussionmentioning
confidence: 81%
“…Upon closer examination, 15 studies were excluded for the following reasons: 4 studies [12][13][14][15] were not case-control or cohort studies, 9 studies did not provide sufficient information to estimate a summary OR and its 95% CI [16][17][18][19][20][21][22][23] or a summary OR adjusted for age. 24 One study 25 evaluated OR and its 95% CI with weight and height, respectively, but no BMI. One study 26 researched the relationship between BPH and BMI in the form of annual growth rates.…”
Section: Resultsmentioning
confidence: 99%
“…29 Some studies reported that a reduction occurs in the hyperplastic prostate mass, primarily of the epithelium, and Weight and benign prostatic hyperplasia A Zucchetto et al with androgen deprivation. [30][31][32][33] A role of androgens in risk of BPH is also supported by the absence of BPH in men castrated before puberty, 34 and by the absent or small prostate in men deficient in 5a-reductase type 2. 35,36 Pharmacological inhibition of dihydrotestosterone, a testosterone metabolite present in the prostate, is associated with a reduction in prostate size, urinary symptoms and surgery for BPH.…”
Section: Discussionmentioning
confidence: 98%